Low Levels of Immunoglobulins and Mannose-Binding Lectin Are Not Associated With Etiology, Severity, or Outcome in Community-Acquired Pneumonia. (5th January 2018) - Siljan, William W; Holter, Jan C; Nymo, Ståle H; Husebye, Einar; Ueland, Thor; Skattum, Lillemor; Bosnes, Vidar; Garred, Peter; Frøland, Stig S; Mollnes, Tom E; Aukrust, Pål; Heggelund, Lars
Abstract: Background: Disease severity and outcome in community-acquired pneumonia (CAP) depend on the host and on the challenge of the causal microorganism(s). We measured levels of immunoglobulins (Igs) and complement in 257 hospitalized adults with CAP and examined the association of low levels of Igs or complement to microbial etiology, disease severity, and short-term and long-term outcome. Methods: Serum Igs were analyzed in blood samples obtained at admission and at 6 weeks postdischarge if admission levels were low. Serum complement deficiencies were screened with a total complement activity enzyme-linked immunosorbent assay (ELISA), with further analyzes performed if justified. Disease severity was assessed by the CURB-65 severity score. Short-term outcome was defined as a composite end point of intensive care unit (ICU) admission and 30-day mortality, and long-term outcome as 5-year all-cause mortality. Results: At admission, 87 (34%) patients had low levels of at least 1 Ig, with low IgG2 as the most prevalent finding (55/21%). IgG levels were lower in bacterial than viral CAP (8.48 vs 9.97 g/L, P = .023), but low Igs were not associated with microbial etiology. Fifty-five (21%) patients had low lectin pathway activity, of which 33 (13%) were mannose-binding lectin (MBL) deficient. Low admission levels of any Ig or MBL were not associated with disease severity, short-term outcome, or long-term outcome. Excluding patients defined as immunocompromised from analysis did not substantially affect these results. Conclusion: In hospitalized adults with CAP, low admission levels of Igs or complement were in general not associated with microbial etiology, disease severity, short-term outcome, or long-term outcome.